Developing Android Developer as an Introduction to the National Hero of East Java - Muhammad Bilal; Nur Khafidhoh (NEWTON: Networking and Information Technology, 2021)
The independence of the Republic of Indonesia did not escape the struggle of the heroes who have valiantly defended the truth, sacrificing themselves for the sake of the integrity of this nation. The task of those of us who have enjoyed the results is to have a moment of silence, remember all his services, and also study seriously. The development of today's world of technology is very influential on the nation's children, because of the many social media applications and games that might make them forget their current joy over the struggles of the heroes of the past. With the development of technology at this time, learning media must also participate to increase stability in the application world. This study aims to build a learning application about the introduction of national heroes in East Java. The design of this game uses the Waterfall method which has 5 stages, namely: Requirements, Design, Implementation, Verification, and Maintenance. The author hopes that by making this learning application, it can assist users to remember the services of the heroes who have fought in the State of Indonesia, and won the independence of the Republic of Indonesia.